(untitled) (Global Journal of Human-Social Science, 2020)
The education sector of a state serves as a basic for its development in different spheres. Thus, the mass media are saddled with the responsibility of presenting a well-rounded report of issues pertaining to the sector as they unfold. This study focused on newspaper coverage of the education sector in Nigeria. The newspapers content analysed were Daily Sun, The Nation, The Guardian and Vanguard. The period studied was 1st January to 30 June, 2017. The research method used was content analysis while agenda setting theory and development media theory served as the theoretical base of the study. The purposive sampling technique was used in arriving at the 208 editions of the four newspapers studied. Findings from the study showed that the newspapers did cover the education sector positively and adequately. The study, also, found that out of the 257 stories on the education sector, 256appeared on the inside pages of the newspapers and 205 were not illustrated. The depth of the stories within 1 -5 inches were 187with news, 196 stories, as the dominant story genre. More so, scholarship/learning has 71 stories which made it the most covered educational issue. Based on the findings of this study, it is recommended among others things that newspapers should endeavour to place essence in the interpretation and analysis of news reports on the education sector.